1999
DOI: 10.1002/(sici)1097-4628(19990110)71:2<267::aid-app10>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponsive polyurethane-acrylate block copolymers. II. Photomechanical effects in copolymers containing 6?-nitro spiropyranes and 6?-nitro-bis-spiropyranes

Abstract: The photochromic effect of polyurethane-acrylate block copolymers containing 6Ј-nitro spiropyranes and 6Јnitro-bis-spiropyranes has been investigated. The influence of incorporation of the photochromic agent into the polymeric matrix as a simple solid solution or via a chemically bonded form and the effect of the composition rate (polyurethane-acrylate) of the block copolymer were studied. In general, it was observed that the photoresponse (photomechanical effect) for the spiropyranes and, especially, the bis-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…They found that λ max of the colored form of spirooxazine was shifted to higher wavelengths in polar matrices, according to the stabilization of metastable zwitterionic isomer by polar interactions with hydroxyl groups in the polymers. In another attempt, the effects of polyurethane–acrylate block copolymers containing SP derivatives on photochromic and photomechanical properties were studied. , It was found that the speed of color fade was inversely dependent on rigidity of the polymeric matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that λ max of the colored form of spirooxazine was shifted to higher wavelengths in polar matrices, according to the stabilization of metastable zwitterionic isomer by polar interactions with hydroxyl groups in the polymers. In another attempt, the effects of polyurethane–acrylate block copolymers containing SP derivatives on photochromic and photomechanical properties were studied. , It was found that the speed of color fade was inversely dependent on rigidity of the polymeric matrix.…”
Section: Introductionmentioning
confidence: 99%
“…In another attempt, the effects of polyurethane−acrylate block copolymers containing SP derivatives on photochromic and photomechanical properties were studied. 35,36 It was found that the speed of color fade was inversely dependent on rigidity of the polymeric matrix. Recently, we have reported the preparation of novel stimuliresponsive papers by modification of cellulosic fibers with functionalized acrylic nanoparticles containing a spiropyran derivative.…”
Section: ■ Introductionmentioning
confidence: 99%